The Implementation of Green Politics by the Government and WWF Indonesia in Aspects of Issue and Policy Orientation - Sinta Apriyani; Utang Suwaryo; Novie Indrawati Sagita (ARISTO, 2024)
The issue of the environmental crisis is increasingly getting the attention of the world community. in addition to the government, the community may also contribute to protecting the environment and saving the earth. moreover, this study used a qualitative approach. a literature study is the data collection technique that was employed. the results of research activities conducted by wwf indonesia obtained outcomes that aligned with the main activities achieved based on the planning that was implemented, regulations formed from activities, and interventions involving stakeholders. thus, the government and wwf indonesia have an impact on each other when it comes to the issue orientation aspect of implementing green politics. furthermore, initiatives from wwf indonesia have the potential to shed light on forest sustainability on the island of kalimantan. however, the environmental movement encompasses more than merely the aspect of realizing policy. every environmentally committed institution also serves the wider community by providing education pertaining to the environment. according to the program table, the program’s implementation for the working period has ended, so it is currently required to clarify the follow-up on which program will be implemented next. this condition also indicates that there was no turning point for the relevant sector government when the responsibility devolved to WWF indonesia, and ultimately, this program was discontinued.